The Merger/Bankruptcy Alternative - Pastena, Victor; Ruland, William (The Accounting Review, 1986)
[Considerable research has examined the ability of accounting information to predict bankruptcy. Bankruptcy, however, represents only one of many possible outcomes for the distressed firm. A timely merger can serve as a bankruptcy alternative. The study compares a sample of distressed firms that merged to a sample of distressed firms that entered bankruptcy. Theory suggests that the owners of distressed firms should prefer merger. The managers, however, may feel that their interests are better served through bankruptcy. The examination focuses upon both firm-related characteristics and the personal interests of owners as determinants of the merger/bankruptcy choice. A probit analysis was used to test the importance of three firm-related variables-revenues, financial leverage, and the magnitude of tax carryforwards in explaining the merger/bankruptcy decision. The examination shows that the distressed firms that merge have lower financial leverage and are larger than firms that enter bankruptcy. Tax carryforwards are not important in the model. We also examined the association of ownership concentration with the merger/bankruptcy choice. The tests reveal that distressed firms with high ownership concentration (or owner control) show an increased tendency to merge rather than to declare bankruptcy. The results suggest that the self interest of managers, rather than just the interests of shareholders and creditors, seems to help motivate the merger/bankruptcy choice.]